Adherence to Artemisinin-Based Combination Therapy for the Treatment of Uncomplicated Malaria: A Systematic Review and Meta-Analysis. (28th May 2015) - Yakasai, Ahmad M.; Hamza, Muhammad; Dalhat, Mahmood M.; Bello, Musa; Gadanya, Muktar A.; Yaqub, Zuwaira M.; Ibrahim, Daiyabu A.; Hassan-Hanga, Fatimah
Abstract : Adherence to artemisinin-based combination therapy (ACT) is not clearly defined. This meta-analysis determines the prevalence and predictors of adherence to ACT. Twenty-five studies and six substudies met the inclusion criteria. The prevalence of ACT adherence in the public sector was significantly higher compared to retail sector (76% and 45%, resp., P < 0.0001 ). However, ACT adherence was similar across different ACT dosing regimens and formulations. In metaregression analysis prevalence estimates of adherence significantly decrease with increasing year of study publicationP = 0.046 . Factors found to be significant predictors of ACT adherence were years of education ≥ 7 odds ratio (OR) (95% CI) = 1.63 (1.05–2.53), higher income 2.0 (1.35–2.98), fatty food 4.6 (2.49–8.50), exact number of pills dispensed 4.09 (1.60–10.7), and belief in traditional medication for malaria 0.09 (0.01–0.78) . The accuracy of pooled estimates could be limited by publication bias, and differing methods and thresholds of assessing adherence. To improve ACT adherence, educational programs to increase awareness and understanding of ACT dosing regimen are interventions urgently needed. Patients and caregivers should be provided with an adequate explanation at the time of prescribing and/or dispensing ACT.